2023
DOI: 10.1002/prop.202200101
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Stability of a New Three Dimensional Regular Black Hole

Abstract: A new model of the regular black hole in dimensions is introduced by considering an appropriate matter field as the energy‐momentum tensor. First, we propose a novel model of d‐dimensional energy density that in dimensions leads to the existence of an upper bound on the radius of the event horizon and a lower bound on the mass of the black hole which are motivated by the features of astrophysical black holes. According to these bounds, we introduce an admissible domain for the event horizon radius, depending o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…Regular black holes are also known to exist in (2 + 1) dimensions [ 11 ]. In particular, configurations with non-linear electrodynamics as an additional matter source have been extensively investigated [ 12 , 13 , 14 , 15 , 16 , 17 ]. In the present work, we will study a 3D black hole that contains as its additional matter sources a cosmological constant and a scalar field.…”
Section: Introductionmentioning
confidence: 99%
“…Regular black holes are also known to exist in (2 + 1) dimensions [ 11 ]. In particular, configurations with non-linear electrodynamics as an additional matter source have been extensively investigated [ 12 , 13 , 14 , 15 , 16 , 17 ]. In the present work, we will study a 3D black hole that contains as its additional matter sources a cosmological constant and a scalar field.…”
Section: Introductionmentioning
confidence: 99%
“…In reference [8], it was demonstrated that the nature of LSM in this model is incompatible with the behavior of nonlinear electrodynamics sources. Also, there's a recent generalization of this latter model in reference [9].…”
Section: Introductionmentioning
confidence: 99%